The "Laterculus Malalianus" and the school of Archbishop Theodore - Stevenson, Jane 1959- (Cambridge Univ. Press, 1995)
The 'Laterculus Malalianus', a historical exegesis of the life of Christ, appears to be the only complete text to survive from the hand of Archbishop Theodore at Canterbury. Its language, style and intellectual frame of reference are thus of great importance for establishing the nature and scope of teaching at Canterbury, the first school of Anglo-Saxon England. The principal lesson of the 'Laterculus' is that though the medium of the Canterbury education was Latin, the content was almost entirely Greek, drawing particularly on the methods of the school of Antioch. It presents a translation of and commentary on the 'Laterculus', and in the introduction Jane Stevenson examines the intellectual milieu of the work, argues the case for attribution to Theodore, and suggests the need for a complete rethinking of the basis of Anglo-Saxon culture.
Keywords: Theodore <of Canterbury, Saint, 602-690>; Theodor -- Canterbury, Erzbischof, Heiliger -- 602-690 -- Laterculus Malalianus; St Augustine's Abbey (Canterbury, England) - History; St. Augustine's Abbey (Canterbury, England) -- History; Laterculus Malalianus; Laterculus Malalianus (Theodorus van Canterbury); Erziehung; Geschichte; Kirchengeschichte; Anglo-Saxons -- England -- Canterbury; Monasticism and religious orders -- Education -- England -- Canterbury -- History; Monasticism and religious orders -- England -- Canterbury -- History -- Middle Ages, 600-1500; England -- Church history -- 449-1066; Kommentar